Automatic transfer switch for DC system application - Hidayat, Mohammad Noor; Wijaya, Wildan Surya; Putri, Ratna Ika (International Journal of Power Electronics and Drive Systems (IJPEDS), 2024)
Automatic transfer switches (ATS) have the potential to be important in ensuring uninterruptible power supply across a wide range of sectors, enabling smooth transitions between utility and emergency RES power sources, generators, and more. Utilizing DC electricity provides a cost advantage and is suitable for short-distance transmission. The author proposes a 12-volt DC backup system that corresponds to a minimum input voltage of more than 10 Vdc and can be applied in various DC load applications. The ATS design incorporates multiple inputs and uses algorithms to prevent simultaneous operation of all sources and reduce feedback. These developments in backup system technology, coupled with the shift to renewable energy, are contributing to the creation of a sustainable and resilient electricity grid. In experiments, the ATS system demonstrated its ability to provide 24 hours of backup power with a specified load (lighting bulbs, light-emitting diodes (LEDs), motors, and fans) discharging 0.27–2.25 Amperes. Using the millis programming language, it supports the performance of a constant switch transition speed of around 0.6453 seconds for a switch from buck to SCC. 0.658 seconds for solar charge controller (SCC) to power supply (PSU), 0.656 seconds for PSU to CC PSU, and 0.61 seconds for PSU to OFF.